Theoretical antecedents and positive employee work experiences of job crafting - Holcombe, Kyla J., author; Byrne, Zinta, advisor; Dik, Bryan, committee member; Eakman, Aaron, committee member; Kraiger, Kurt, committee member (Colorado State University. Libraries, 2016)
Although there have been recent advances in the conceptualization of job crafting (e.g., Berg, Dutton, & Wrzesniewski, 2013; Leana, Appelbaum, & Shevchuk, 2009) and in mapping its nomological network (Berg, Dutton & Wrzesniewski, 2007; Demerouti & Bakker, 2014; Petrou, 2013), the theory of job crafting remains limited. Specifically, job crafting theory fails to recognize important theoretical antecedents of job crafting behavior, including individual, work context, and leadership factors that serve as sources of motivation for employee job crafting. Furthermore, the theory does not explain the complex interrelationship of job crafting and traditional work design (Hackman & Oldham, 1976; Humphrey, Nahrgang, & Morgeson, 2007), even though job crafting is said to complement and supplement traditional work design to influence employee work experiences (Berg et al., 2013). Through this study, I expand job crafting theory to not only rely on a needs-based approach to motivation (Berg et al., 2013; Wrzesniewski & Dutton, 2001), but to also apply cognitive, trait/dispositional, behavioral, and work design approaches to understand why employees are motivated to craft in their work roles. Study hypotheses were investigated using a sample of working adults and their colleagues (N = 120 employee-colleague dyads), both of whom provided information about individual, leader, and work characteristics, as well as ratings of job crafting behaviors, work attitudes, motivation, and adaptive performance. Results show individual factors (i.e., proactivity and learning orientation), work design factors (i.e., task and social characteristics), and leader factors (empowerment and trust) all significantly relate to job crafting and should be conceptualized as theoretical precursors to job crafting. Additionally, job crafting and work design factors predict positive employee work experiences. Specifically, task characteristics and job crafting explain significant variance in employees’ intrinsic motivation; task and social characteristics explain significant variability in person-organization fit; and as a final indicator of positive work experiences, employee adaptive performance is significantly related to knowledge characteristics. The findings of this study advance job crafting and work design theories and provide practical recommendations for facilitating positive work experiences through both job crafting and work design efforts.